Hip implant modular junction: The role of CoCrMo alloy microstructure on fretting-corrosion. (October 2022) - Manthe, Jacob; Cheng, Kai Yuan; Bijukumar, Divya; Barba, Mark; Pourzal, Robin; Neto, Mozart; Mathew, Mathew T.
Abstract: Cobalt-chromium-molybdenum (CoCrMo) alloy is one of the most used metals in total hip replacement (THR) due to the alloy's superior corrosion qualities and biocompatibility. Over time these prostheses may undergo wear and corrosion processes in a synergistic process known as tribocorrosion. Implant retrieval studies have shown that damage patterns on THR modular junction surfaces indicating specifically in vivo fretting-corrosion to take place. To date, there have been no studies on the fretting-corrosion behaviors of CoCrMo alloy under the consideration of specific microstructural features. A custom-built flat-on-flat fretting-corrosion setup was utilized to test the synergistic tribocorrosion behavior of fretting-corrosion. The difference in microstructure was generated through the cutting orientations of the transverse and the longitudinal direction of the bar stock material, where the longitudinal cut exhibits a characteristic banded microstructure (banded group) and the transverse cut a homogenous microstructure (unbanded group). A three-electrode system was employed to monitor the induced currents. Two different types of electrolytes were used in the current study: 1. Bovine calf serum (BCS-30 g/L protein) (normal conditions) 2. BCS with Lipopolysaccharide (LPS, 0.15 μg/ml) (simulated infectious conditions). In the free potential mode, banded samples showed an increased potential compared to the unbanded samples. In potentiostatic conditions, the banded group also exhibited a higher induced current in both electrolyte environments, indicating more corrosion loss. Both Nyquist and Bode plots showed both orientations of metal becoming more corrosion resistant post-fretting when compared to pre-fretting data. The longitudinal group at OCP demonstrated a unique shape of the fretting-loop, which might be related to tribochemical reactions. Based on the mechanical, electrochemical, and surface characterization data, the transverse group (unbanded) microstructures demonstrates a higher resistance to fretting-corrosion damage.